The great mimic: syphilis mimicking testicular tumour. Conservative management using antibiotics alone with testicular sparing. (May 2013) - Teo, S Y; Morris, G; Fairley, I
Summary: We present the case of a 47-year-old man who attended a genitourinary (GU) medicine clinic with posthitis and a painless testicular mass on examination. Initial ultrasound revealed a 2-cm well-defined hypoechoic mass within the right testis and he was referred to urology on suspicion of malignancy. Subsequent syphilis serology was positive and the penile lesion and testicular mass were felt to be consistent with syphilis. After liaising with the urology department, and in view of negative tumour markers (lactate dehydrogenase, alfa-fetoprotein and human chorionic gonadotrophin) and known penicillin allergy, he was managed conservatively with four weeks of oral doxycycline. Follow-up ultrasound scans revealed adequate response of the testicular mass, with the last scan, performed at 10 months post-treatment, showing complete resolution. This is the first documented case of conservative management of a testicular syphilitic lesion using antibiotics alone with testicular sparing.